Evaluation and Comparison of 2 On‐Farm Tests for Estimating Somatic Cell Count in Quarter Milk Samples from Lactating Dairy Cattle. (9th December 2017) - Kandeel, S.A.; Megahed, A.A.; Arnaout, F.K.; Constable, P.D.
Abstract : Background: The somatic cell count (SCC) is commonly used to monitor udder health and diagnose subclinical intramammary infection (IMI) in dairy cattle. Hypothesis: The Somaticell test (ST)2 and California mastitis test (CMT) are clinically useful cow‐side tests for diagnosing subclinical IMI. Animals: One hundred and eleven dairy cows at dry‐off and 92 cows within 4–7 days postcalving. Methods: Quarter foremilk samples were obtained and analyzed with a DeLaval cell counter (DCC, reference method), ST, and CMT. The ST was run in a simulated cow‐side manner using milk at 37°C instead of 0–8°C as recommended by the manufacturer. Test performance for diagnosing IMI (DCC SCC >200, 000 cells/mL) was evaluated by calculating the area under the receiver operating characteristic curve (AUC) and the kappa coefficient (κ) at the optimal cut‐point for each test. The effect of milk/reagent temperature also was evaluated. Results: Compared to the reference method, the ST run in a simulated cow‐side manner had an AUC = 0.68 and κ = 0.24 at dry‐off, and AUC = 0.74 and κ = 0.40 in fresh cows. The CMT performed much better than the ST in diagnosing subclinical IMI with AUC = 0.88 and κ = 0.77 at dry‐off, and AUC = 0.87 and κ = 0.76 in fresh cows. The measured ST value decreased with increasing temperature of the milk/reagent mixture. Conclusions/Clinical Importance: The ST is optimized for use on milk at 0–8°C and is therefore designed for on‐farm use on refrigerated milk samples. The ST is not suited for use as a cow‐side screening test for IMI because the milk temperature exceeds the recommended range for the test.